Auditory evoked arousal responses of 3‐month‐old infants exposed to methamphetamine in utero: a nap study. (29th January 2013) - Galland, Barbara C; Mitchell, Ed A; Thompson, John MD; Wouldes, Trecia; ,
Abstract Aim To investigate whether or not infants exposed to methamphetamine prenatally have impaired arousal responses from sleep. Methods The polygraphic nap studies involved 42 infants aged 3 months exposed to methamphetamine in utero and a comparison group of 57 infants. A proportion of mothers in both groups smoked cigarettes and/or marijuana and drank alcohol during pregnancy. White noise from 50 to 100 decibels (dB) was administered at 10 dB intervals twice within non‐rapid eye movement (NREM) and rapid eye movement (REM) sleep states and arousal thresholds measured. Results Combining groups, 306 tests were completed (128 and 178 within REM and NREM sleep, respectively) and infants were more likely to wake at lower thresholds in REM than NREM sleep (hazard ratio 5.58; 95% CI, 3.78–8.23 p < 0.0001). No significant differences in arousal threshold were found between methamphetamine and comparison groups, before or after controlling for other substance use (NREM sleep; 0.98, 95% CI, 0.60–1.59 and REM sleep; 1.03, 95% CI, 0.56–1.89). Conclusions These findings suggest that arousal responses of methamphetamine‐exposed infants remain intact, providing no support for the hypothesis that prenatal exposure could increase their vulnerability to sudden infant death syndrome (SIDS) through arousal deficits.